De Novo Production of Glycyrrhetic Acid 3-O-mono-β-D-glucuronide in Saccharomyces cerevisiae - Huang, Ying; Jiang, Dan; Ren, Guangxi; Yin, Yan; Sun, Yifan; Liu, Tengfei; Liu, Chunsheng (Frontiers in Bioengineering and Biotechnology, 2021)
Glycyrrhetic acid 3-O-mono-β-D-glucuronide (GAMG) is a rare compound in licorice and its short supply limits the wide applications in the pharmaceutical, cosmetic, and food industries. In this study, de novo biosynthesis of GAMG was achieved in engineered Saccharomyces cerevisiae strains based on the CRISPR/Cas9 genome editing technology. The introduction of GAMG biosynthetic pathway resulted in the construction of a GAMG-producing yeast strain for the first time. Through optimizing the biosynthetic pathway, improving the folding and catalysis microenvironment for cytochrome P450 enzymes (CYPs), enhancing the supply of UDP-glucuronic acid (UDP-GlcA), preventing product degradation, and optimizing the fermentation conditions, the production of GAMG was increased from 0.02 μg/L to 92.00 μg/L in shake flasks (4,200-fold), and the conversion rate of glycyrrhetic acid (GA) to GAMG was higher than 56%. The engineered yeast strains provide an alternative approach for the production of glycosylated triterpenoids.